A super hydrophobic coating and its preparation method and application
By using a small amount of hydrophobic modifier and high solid aqueous film forming resin in the preparation of superhydrophobic coatings, the problems of high cost, low efficiency and waste liquid generation in the prior art are solved, and a more efficient and environmentally friendly super Hydrophobic coating preparation.
Patent Information
- Application Number
- CN202311705519.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-12-12
AI Technical Summary
The existing preparation methods for superhydrophobic coatings require a large amount of hydrophobic substances and long-term heating and stirring, resulting in high cost, low efficiency, and a large amount of waste liquid and high energy consumption.
A small amount of hydrophobic modifier and a gentle process are used to modify the inorganic micro-nano particles at a low degree, and directly mix it with a high solid aqueous film-forming resin to form a superhydrophobic coating.
The dispersion of inorganic micro-nano particles in the coating and uniformity during coating are improved, precipitation and compatibility problems are avoided, preparation costs and energy consumption are reduced, and environmentally friendly.
Smart Images

Figure CN117887313B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of super hydrophobic coatings, and in particular to a super hydrophobic coating and a preparation method and application thereof. Background Art
[0002] The coating with surface water contact angle>150°, rolling angle<10° can be called super hydrophobic coating, and there are many methods for making it, and coating method is one of them. Coating method can be divided into single coating method and double (multi) coating method. The common practice of making super hydrophobic coating with single coating coating method is: disperse and modify the inorganic particles of micro-nano size in liquid phase with hydrophobic substance, then separate liquid and solid, dry, obtain hydrophobic modified particles, and disperse in various film-forming materials, that is, obtain super hydrophobic coating. Coating forms coating on various substrates by spraying, scraping and other methods, and finally dries and solidifies to obtain super hydrophobic coating. However, the acquisition method of this super hydrophobic coating usually needs to add a large amount of hydrophobic substance and combine acid or ammonia for a long time heating and stirring, so as to obtain a higher degree of modification so as to enhance hydrophobicity, resulting in high cost and low efficiency of preparation; and a large amount of waste liquid will be produced during liquid-solid separation of hydrophobic modified particles, and it is easy to reunite and high energy consumption during drying. Summary of the invention
[0003] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application proposes a super hydrophobic coating and a preparation method and application thereof, wherein the preparation process is simple, fast, low-cost and high-efficiency.
[0004] In a first aspect of the present application, a method for preparing a super hydrophobic coating is provided, comprising the following steps:
[0005] A hydrophobic modifier is mixed with a dispersion of inorganic micro-nano particles to react to obtain a dispersion of hydrophobically modified inorganic micro-nano particles, wherein the mass of the hydrophobic modifier is 10 to 50% of the mass of the inorganic micro-nano particles, and the hydrophobic modifier includes at least one of alkyl silane, fluorosilane, and perfluoropolyether silane;
[0006] The dispersion of hydrophobically modified inorganic micro-nano particles is mixed with a high-solid aqueous film-forming resin to obtain a super-hydrophobic coating, wherein the high-solid aqueous film-forming resin has a solid content of more than 50%.
[0007] The preparation method according to the embodiment of the present application has at least the following beneficial effects:
[0008] In the embodiment of the present application, a small amount of hydrophobic modifier and a mild process are selected to modify the inorganic micro-nano particles to a low degree, and the use of a high-solid water-containing film-forming resin is directly combined to make the modified inorganic micro-nano particles have better dispersibility in the coating and uniformity during coating, avoiding the problem of precipitation and poor compatibility with resins due to the high hydrophobic modification degree of nanoparticles in the prior art, and also avoiding the problem of large amounts of fluorine-containing waste liquid generated by liquid-solid separation, high energy consumption and secondary agglomeration caused by drying. The dispersibility of inorganic micro-nano particles is improved at the expense of the degree of modification, so that the hydrophobic effect is more fully exerted when using less hydrophobic substances. The entire preparation process is simpler, faster, less costly and more efficient.
[0009] In some embodiments of the present application, the solvent in the dispersion of inorganic micro-nano particles includes isopropanol and ethanol. The introduction of isopropanol as an additional solvent can properly adjust the film-forming properties of the coating, and the hydrophobic modifier has a certain solubility in both solvents, so that the hydrophobically modified inorganic micro-nano particles can have a better dispersion effect during the preparation process of the coating and when forming the coating, thereby improving the realization of its super-hydrophobic effect.
[0010] In some embodiments of the present application, the mass percentage of the inorganic micro-nano particles in the dispersion of the inorganic micro-nano particles is 2-6%, for example, 2%, 3%, 4%, 5%, or 6%.
[0011] In some embodiments of the present application, the mass percentage of isopropanol in the dispersion of inorganic micro-nanoparticles is 1-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%.
[0012] In some embodiments of the present application, the inorganic micro-nano particles include at least one of silicon dioxide, aluminum oxide, zinc oxide, titanium dioxide, and silicon carbide.
[0013] In some embodiments of the present application, the hydrophobic modifier includes at least one of an alkylsilane, a fluorosilane, and a perfluoropolyether silane. The alkylsilane may be, for example, hexadecyltrimethoxysilane (HDTMS), octadecyltrichlorosilane (OTS), etc., and the fluorosilane may be, for example, heptadecafluorodecyltrimethoxysilane, 1H,1H,2H,2H-perfluorodecyltrichlorosilane, etc.
[0014] In some embodiments of the present application, the time for the mixing reaction of the hydrophobic modifier and the dispersion of the inorganic micro-nano particles is 2 to 4 hours.
[0015] In some embodiments of the present application, the temperature for the mixing reaction of the hydrophobic modifier and the dispersion of the inorganic micro-nanoparticles is 20-40°C, for example, it can be room temperature 23±2°C, 25±5°C, 20±5°C.
[0016] In some embodiments of the present application, the raw material of the mixed reaction with the dispersion of inorganic micro-nano particles also includes a silane coupling agent. The hydroxyl dehydration condensation of the silanol after the hydrolysis of the silane coupling agent and the inorganic micro-nano particle surface forms a chemical grafting, and the epoxy group at its end reacts with the hydroxyl in the high solid content water-based film-forming resin to form a chemical bond, enhancing the compatibility and bonding strength of the inorganic micro-nano particles and the resin, thereby further improving the dispersibility of the inorganic micro-nano particles, and improving the super-hydrophobic effect and mechanical properties of the super-hydrophobic coating. It is understandable that, according to the type of the inorganic micro-nano particles and the type of the film-forming resin, the type and dosage of the silane coupling agent are also different.
[0017] In some embodiments of the present application, the silane coupling agent includes at least one of trimethylchlorosilane, dimethyldichlorosilane, methyltrichlorosilane, trimethylethoxysilane, dimethyldiethoxysilane, γ-aminopropyltriethoxysilane (KH-550), γ-glycidyloxypropyltrimethoxysilane (KH-560), vinyltrimethoxysilane, etc.
[0018] In some embodiments of the present application, the mass of the silane coupling agent is 10 to 50 wt % of the mass of the inorganic micro-nano particles.
[0019] In some embodiments of the present application, the solid content of the high-solid aqueous film-forming resin is 50%, 55%, 60%, 65%, 70% or more. The high-solid content resin is used to introduce only a small amount of solvent water into the coating system, and to avoid turbidity or precipitation caused by incompatibility of the system as much as possible, thereby improving the dispersibility of the inorganic micro-nano particles and improving the super-hydrophobicity and mechanical properties of the final film.
[0020] In some embodiments of the present application, the high-solid aqueous film-forming resin includes at least one of an aqueous acrylic resin and an aqueous amino resin.
[0021] In some embodiments of the present application, the high-solid water-based film-forming resin includes at least one of a water-based acrylic resin, a water-based amino resin, a water-based alkyd resin, a water-based epoxy resin, a water-based fluorocarbon resin, and the like.
[0022] In some embodiments of the present application, the high-solid aqueous film-forming resin includes an aqueous acrylic resin and an aqueous amino resin. In addition to being a film-forming resin, the aqueous amino resin also acts as a curing agent to undergo a cross-linking reaction, and reacts with a coupling agent to enhance the bonding strength with the inorganic micro-nano particles, thereby enhancing the effect of the coupling agent.
[0023] In some embodiments of the present application, the mass of the water-based acrylic resin is 1.5 to 7 times the mass of the inorganic micro-nanoparticles.
[0024] In some embodiments of the present application, the mass of the water-based amino resin is 0.35 to 1.8 times the mass of the inorganic micro-nano particles.
[0025] In some embodiments of the present application, a leveling agent is further added when the dispersion of hydrophobically modified inorganic micro-nano particles is mixed with the high-solid aqueous film-forming resin.
[0026] In some embodiments of the present application, the mass of the leveling agent does not exceed 5% of the mass of the inorganic micro-nano particles.
[0027] The second aspect of the present application provides a super hydrophobic coating, which is prepared by any of the aforementioned preparation methods.
[0028] According to a third aspect of the present application, a method for forming a super-hydrophobic coating is provided, comprising applying the aforementioned super-hydrophobic coating to a substrate and curing to obtain a super-hydrophobic coating.
[0029] In some embodiments of the present application, the curing step includes pre-curing at 50-80° C. and curing at 150-200° C. The pre-curing temperature may be, for example, 50° C., 60° C., 70° C., 80° C., and the curing temperature may be, for example, 150° C., 160° C., 170° C., 180° C., 190° C., 200° C.
[0030] In some embodiments of the present application, the pre-curing time is 10 to 20 minutes, for example, 10 minutes, 15 minutes, or 20 minutes.
[0031] In some embodiments of the present application, the formal curing time is 10 to 60 minutes, for example, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or 60 minutes.
[0032] In some embodiments of the present application, the curing step includes pre-curing at 50-80° C. for 10-20 min and final curing at 150-200° C. for 10-60 min, performed sequentially.
[0033] In some embodiments of the present application, the substrate includes at least one of glass, metal, cement, plastic, fabric, paper, etc.
[0034] In some embodiments of the present application, the method of applying the superhydrophobic coating to the substrate includes at least one of spraying, scraping, spin coating, wiping, brushing, dipping, etc.
[0035] In a fourth aspect of the present application, a super-hydrophobic coating is provided, wherein the super-hydrophobic coating is formed according to any of the aforementioned formation methods.
[0036] The fifth aspect of the present application provides a coating product, comprising a substrate and any one of the aforementioned superhydrophobic coatings.
[0037] In the embodiments of the present application, it is found that the degree of modification of inorganic nanoparticles and their degree of dispersion in the resin have a greater influence on the super-hydrophobic effect of the super-hydrophobic coating formed by the final super-hydrophobic coating. After the modification reaches a certain degree (for example, TGA weight loss reaches 10%), the influence of the degree of dispersion on the super-hydrophobic effect is greater than the degree of modification. At this time, excessive modification should not be pursued, otherwise the disadvantage caused by the deterioration of the degree of dispersion will be greater than the advantage brought by the degree of modification. Therefore, the preparation method provided by the embodiment of the present application highlights the importance of the degree of dispersion; in addition, due to the low degree of modification, some hydrophobic substances are not grafted onto inorganic micro-nano particles and are in a free state. Due to the lack of liquid-solid separation, this part of the hydrophobic substances is utilized to participate in film formation, further ensuring the hydrophobicity of the coating as a whole.
[0038] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is the measurement result of the contact angle in one embodiment of the present application.
[0040] Figure 2 is an electron microscope image of a super-hydrophobic coating formed in one embodiment of the present application. DETAILED DESCRIPTION
[0041] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.
[0042] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.
[0043] In the description of this application, "several" means more than one, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0044] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein are only for the purpose of describing the embodiments of this application and are not intended to limit this application.
[0045] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples" or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0046] Some of the raw materials involved in the following examples are described as follows:
[0047] Fumed silica (hydrophilic type): Cabot M-5, primary particle size 12 nm;
[0048] Acrylic resin: HOMAAC-5201, solid content about 50%, Zhuhai Jintuan Chemical Co., Ltd.
[0049] Amino resin: Cytec 325, solid content about 80%;
[0050] Leveling agent: BYK-333.
[0051] Example 1
[0052] The present embodiment provides a method for preparing a super hydrophobic coating and a super hydrophobic coating, comprising the following steps:
[0053] (1) Weigh 4 g of fumed silica, add 5 g of isopropanol and 91 g of anhydrous ethanol, totaling 100 g, and disperse with a stirrer equipped with a dispersion disk at high speed. The diameter of the dispersion disk is 6 cm, the stirring speed is 2000 rpm, and the stirring time is 1 h to obtain a dispersion of nano-silica.
[0054] (2) Add 0.75 g of heptadecafluorodecyltrimethoxysilane and 0.25 g of γ-glycidyloxypropyltrimethoxysilane (KH560) to the nano-silica dispersion, and stir at room temperature for 3 h to obtain a hydrophobically modified nano-silica dispersion.
[0055] (3) Add 9.5 g of acrylic resin, 2.4 g of amino resin, and 0.1 g of leveling agent to the dispersion of hydrophobically modified nano-silica, and stir at 350 rpm for 10 min to obtain a super hydrophobic coating.
[0056] (4) A cleaned glass substrate is provided, and the super-hydrophobic coating is coated on the surface of the glass substrate by scraping, and then pre-cured at 60° C. for 15 min, and then cured at 180° C. for 30 min, to obtain a super-hydrophobic coating sample.
[0057] In this example, the amount of the hydrophobic modifier (heptadecafluorodecyltrimethoxysilane) added is 18.75% of the mass of the silica, and the theoretical calculation of TGA weight loss is 13-15%, but the actual TGA weight loss detected is only 11.5%, indicating that the hydrophobic modifier is not completely modified with the fumed silica, but a certain amount of free is retained in the dispersion.
[0058] Example 2
[0059] This comparative example provides a super-hydrophobic coating and a super-hydrophobic coating, which are different from Example 1 in that the mass of heptadecafluorodecyltrimethoxysilane in the preparation process is 1 g.
[0060] Example 3
[0061] This comparative example provides a super-hydrophobic coating and a super-hydrophobic coating, which are different from those of Example 1 in that the mass of the acrylic resin in the preparation process is 11.4 g, and the mass of the amino resin is 2.9 g.
[0062] Comparative Example 1
[0063] This comparative example provides a method for preparing a super-hydrophobic coating, comprising the following steps:
[0064] (1) Weigh 2 g of fumed silica, add 96 g of anhydrous ethanol, a total of 98 g, and disperse with a stirrer equipped with a dispersion disk at high speed. The diameter of the dispersion disk is 6 cm, the stirring speed is 2000 rpm, and the stirring time is 1 h to obtain a dispersion of nano-silica.
[0065] (2) Add 4 g of heptadecafluorodecyltrimethoxysilane, 1 g of KH560 and 2 g of ammonia water to the nano-silica dispersion, stir at 60° C. for 6 h to obtain a hydrophobically modified nano-silica dispersion, then centrifuge, spray dry and crush to obtain hydrophobically modified nano-silica powder.
[0066] (3) Take 1 g of hydrophobically modified nano-silica powder, add 18 g of butyl acetate, and perform ultrasonic treatment for 30 min. Then, add 2.7 g of oily composite resin (solid content of about 50%) under stirring conditions, and stir for another 10 min to obtain a super hydrophobic coating.
[0067] (4) providing a cleaned glass substrate, coating the super hydrophobic coating on the surface of the glass substrate by scraping, and then pre-curing at 60° C. for 15 min, and then curing at 150° C. for 30 min, to obtain a super hydrophobic coating sample.
[0068] Comparative Example 2
[0069] This comparative example provides a method for preparing a super-hydrophobic coating. Compared with comparative example 1, the only difference is that heptadecafluorodecyltrimethoxysilane is 0.75 g and KH560 is 0.25 g.
[0070] Comparative Example 3
[0071] This comparative example provides a method for preparing a super-hydrophobic coating. Compared with comparative example 1, the only difference is that after obtaining the dispersion of hydrophobically modified nano-silica, the steps of centrifugation, spray drying and crushing are omitted, and step (3) is directly performed.
[0072] Comparative Example 4
[0073] This comparative example provides a method for preparing a super-hydrophobic coating. Compared with comparative example 1, the only difference is that after obtaining a dispersion of hydrophobically modified nano-silica, the steps of centrifugation, spray drying, and crushing are omitted, and step (3) is directly performed, and the oily composite resin is replaced with an acrylic resin and an amino resin with the same total solid content and ratio as in Example 1.
[0074] The super-hydrophobic coatings of the embodiment and the comparative example were tested respectively, and the method was as follows:
[0075] Contact angle: 2 μL of deionized water was dropped onto the surface of a horizontally placed glass substrate with a super-hydrophobic coating to form a water droplet, and the contact angle of the water droplet was measured.
[0076] Rolling angle: 5 μL of deionized water is added to the surface of a horizontally placed glass substrate with a superhydrophobic coating to form a water droplet. The glass substrate is slowly tilted until the water droplet rolls. The tilt angle of the glass substrate at this time is measured as the rolling angle.
[0077] Water flow impact test: The surface of the glass substrate with super hydrophobic coating is impacted by water flow at a flow rate of 4 m / s for 5 min. After the impact, the contact angle and rolling angle of the super hydrophobic coating are tested to see if they change.
[0078] Wet-dry cycle experiment: Place the glass substrate with super-hydrophobic coating in a lifting device, gradually lower it until the glass substrate is completely immersed in water, stay for 1 second, then rise, and stay for 4 minutes after the glass substrate is completely out of the water, which is considered as one cycle. After repeating 6000 times, observe whether there is scale on the surface.
[0079] The test results are shown in the following table:
[0080] Table 1. Setup and test results of examples and comparative examples
[0081]
[0082] By controlling the amount of the water-based resin in the example and the amount of the oily resin in the comparative example, the relative content of silicon dioxide in the super-hydrophobic coatings formed in the above examples 1 to 3 and comparative examples 1 and 2 is basically the same.
[0083] The contact angle measurement results of Example 1 are combined with Figure 1 From the above results, it can be seen that the super-hydrophobic coating provided in the embodiment has super-hydrophobic properties, water flow impact resistance and dry-wet cycle resistance that are relatively consistent with the existing super-hydrophobic coating.
[0084] The electron microscopy results of the super hydrophobic coating prepared in Example 1 are as follows: Figure 2 As shown, a large number of uniform rough micro-nano structures are formed on the coating surface, and the appearance is good. In contrast, the silicon dioxide particles in Examples 2 and 3 are slightly agglomerated, and the appearance of the film is slightly poor.
[0085] In Comparative Example 3, when the oily resin was directly added, due to the excessive alcohol content, the resin was still difficult to disperse after multiple stirring treatments such as ultrasound, and the final coating was uneven, and the super hydrophobicity, water flow impact resistance, and dry-wet cycle resistance were far inferior to Examples 1 to 3 or Comparative Example 1. In Comparative Example 4, a water-based resin was added, but due to excessive modification, the silica particles had been precipitated, and it was still difficult to stir after multiple stirring treatments such as ultrasound, and the final coating was uneven, and the super hydrophobicity, water flow impact resistance, and dry-wet cycle resistance were far inferior to Examples 1 to 3 or Comparative Example 1.
[0086] In combination with the embodiments and comparative examples, it is found during the experiment that when a hydrophobic substance is used to disperse and modify the inorganic particles of micro-nano size in the liquid phase, a large amount of hydrophobic substances are usually added, and heated and stirred for a long time under acidic or alkaline conditions, so that the inorganic particles obtain a higher degree of modification (for example, the hydrophobically modified nano-silicon dioxide powder in comparative example 1 is subjected to TGA test, and the temperature is increased from 40°C to 900°C, and the weight loss is 20-30%, while the weight loss of the nano-silicon dioxide in the dispersion is <2% for the same test) to enhance hydrophobicity, but this leads to high cost and low efficiency during preparation. Moreover, the modified nano-silicon dioxide needs liquid-solid separation, produces waste liquid, is not environmentally friendly, and has high energy consumption and high cost during drying; if the oily resin is directly added without separation, it is incompatible with the original ethanol solvent, and if the general water-based resin is directly added, the introduction of a large amount of water will be incompatible with the hydrophobic substance; if the resin is not added, the mechanical properties are poor. In addition, the high degree of hydrophobic modification of inorganic particles can easily lead to precipitation during the modification process, and further agglomeration after drying, which ultimately makes it difficult to disperse the modified inorganic particles in the resin, and even more difficult in the water-based resin, so the hydrophobic effect cannot be fully exerted.
[0087] In the embodiment, when the hydrophobic substance is used to disperse and modify the micro-nano-sized inorganic particles in the liquid phase, excessive modification is not pursued, only a small amount of hydrophobic substance is added, no acid, alkali or heating is required, and only a short period of stirring is performed, so that the cost required for preparation is lower, the use of the more expensive hydrophobic substance is reduced, and the efficiency is higher. The modified inorganic particles are not subjected to liquid-solid separation, and the resin is directly added, no waste liquid is generated, and no drying process is required, which is environmentally friendly and has low energy consumption.
[0088] Due to the small amount of hydrophobic substance added, the degree of modification is not high (for example, hydrophobic modified nano silicon dioxide powder in Examples 1 to 3 is subjected to TGA test, and the temperature is increased from 40°C to 900°C, and the weight loss is <15%, and Example 1 is 11.5%), and the inorganic particles do not produce precipitation in the process of preparation and coating, and no obvious agglomeration occurs due to drying. The solid content of the aqueous resin added at the same time is high, and the water content is relatively small, so it will not cause the uniformity of the inorganic particles dispersion due to incompatibility with a small amount of hydrophobic substances in the dispersion liquid. Adding an appropriate amount of resin that can be cross-linked with inorganic particles during curing has little effect on super-hydrophobicity, but significantly improves mechanical properties. Therefore, the modified inorganic particles are well dispersed in the liquid phase, and have good compatibility with the added resin. Compared with the related art, although the degree of modification is sacrificed, the dispersion is improved, and its hydrophobic effect is more fully exerted in the case of less hydrophobic substances.
[0089] Example 4
[0090] This embodiment provides a super-hydrophobic coating and a super-hydrophobic coating made of the super-hydrophobic coating. The difference from Example 1 is that KH560 is replaced by KH550 of equal mass, and the amount of acrylic resin is 7g, and the amount of amino resin is 4g.
[0091] Embodiments 5 to 8
[0092] This embodiment provides a super-hydrophobic coating and a super-hydrophobic coating made of the super-hydrophobic coating. The difference from Example 1 is that the dispersion of nano-silicon dioxide is replaced by dispersions of nano-aluminum oxide, micron zinc oxide, nano-titanium dioxide, and nano-silicon carbide, respectively.
[0093] Embodiments 9-10
[0094] This embodiment provides a super-hydrophobic coating and a super-hydrophobic coating made of the super-hydrophobic coating. The difference from Embodiment 1 is that heptadecafluorodecyltrimethoxysilane is replaced by hexadecyltrimethoxysilane and perfluoropolyether silane of equal mass, respectively.
[0095] Examples 11 to 13
[0096] This embodiment provides a super-hydrophobic coating and a super-hydrophobic coating made of the super-hydrophobic coating. The difference from Example 1 is that the water-based acrylic resin is replaced by a water-based alkyd resin, a water-based epoxy resin, and a water-based fluorocarbon resin of the same solid weight.
[0097] The super-hydrophobic coatings prepared in Examples 4 to 13 were tested using the above-mentioned detection method and found to have super-hydrophobic properties, water flow impact resistance and dry-wet cycle resistance similar to those of Example 1, which will not be repeated here.
[0098] The present application is described in detail above in conjunction with the embodiments, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
Claims
1. A method for preparing a super hydrophobic coating, characterized in that: Here are the steps: A hydrophobic modifier, a silane coupling agent and a dispersion of inorganic micro-nano particles are mixed and reacted to obtain a dispersion of hydrophobically modified inorganic micro-nano particles, wherein the mass of the hydrophobic modifier is 10% to 25% of the mass of the inorganic micro-nano particles; The dispersion of the hydrophobically modified inorganic micro-nano particles is mixed with a high-solid aqueous film-forming resin and a leveling agent to obtain the super-hydrophobic coating, wherein the solid content of the high-solid aqueous film-forming resin is more than 55%, and the high-solid aqueous film-forming resin includes an aqueous acrylic resin and an aqueous amino resin, wherein the mass of the aqueous acrylic resin is 1.5 to 7 times the mass of the inorganic micro-nano particles, and the mass of the aqueous amino resin is 0.35 to 1.8 times the mass of the inorganic micro-nano particles; Wherein, the dispersion of the inorganic micro-nano particles is composed of inorganic micro-nano particles and a solvent, and the solvent is isopropanol and ethanol; The mass percentage of the inorganic micro-nano particles in the dispersion of the inorganic micro-nano particles is 2-6%; The mass percentage of isopropanol in the dispersion of the inorganic micro-nano particles is 1-10%; The inorganic micro-nano particles are at least one of nano-silicon dioxide, nano-aluminum oxide, nano-titanium dioxide, and nano-silicon carbide; The hydrophobic modifier is at least one of alkyl silane, fluorosilane and perfluoropolyether silane, the alkyl silane is hexadecyltrimethoxysilane and octadecyltrichlorosilane, the fluorosilane is heptadecafluorodecyltrimethoxysilane and 1H,1H,2H,2H-perfluorodecyltrichlorosilane; The time for the mixing reaction of the hydrophobic modifier and the dispersion of the inorganic micro-nano particles is 2-4 hours, and the temperature of the mixing reaction is 20-40° C.; The mass of the silane coupling agent is 10-50wt% of the mass of the inorganic micro-nano particles, and the silane coupling agent is KH550 or KH560.
2. The preparation method according to claim 1, characterized in that: The mass of the leveling agent does not exceed 5% of the mass of the inorganic micro-nano particles.
3. the super-hydrophobic coating prepared by the preparation method described in any one of claims 1 to 2.
4. A method for forming a super hydrophobic coating, characterized in that: The super-hydrophobic coating according to claim 3 is applied to a substrate and cured to obtain a super-hydrophobic coating.
5. The forming method according to claim 4, characterized in that: The curing step includes pre-curing at 50-80°C and formal curing at 150-200°C, which are performed sequentially.
6. The forming method according to claim 5, characterized in that: The pre-curing time is 10 to 20 minutes.
7. The forming method according to claim 5, characterized in that: The formal curing time is 10 to 60 minutes.
8. A super-hydrophobic coating formed by the formation method according to any one of claims 4 to 7.
9. A coated product, characterized in that Comprising a substrate and the super-hydrophobic coating according to claim 8.
Citation Information
Patent Citations
Waterborne polyurethane super-hydrophobic coating and preparation method thereof
CN108047916A